2008
DOI: 10.1074/jbc.m806446200
|View full text |Cite
|
Sign up to set email alerts
|

Mutations Define Cross-talk between the N-terminal Nucleotide-binding Domain and Transmembrane Helix-2 of the Yeast Multidrug Transporter Pdr5

Abstract: The yeast Pdr5 multidrug transporter is an important member of the ATP-binding cassette superfamily of proteins. We describe a novel mutation (S558Y) in transmembrane helix 2 of Pdr5 identified in a screen for suppressors that eliminated Pdr5-mediated cycloheximide hyper-resistance. Nucleotides as well as transport substrates bind to the mutant Pdr5 with an affinity comparable with that for wild-type Pdr5. Wild-type and mutant Pdr5s show ATPase activity with comparable K m(ATP) values. Nonetheless, drug sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
119
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(125 citation statements)
references
References 36 publications
6
119
0
Order By: Relevance
“…We introduced the mutant plasmid DNA into R-1 with a Sigma-Aldrich yeast transformation kit. Genetic testing confirmed that the construct was correctly inserted (17).…”
Section: Methodsmentioning
confidence: 82%
See 4 more Smart Citations
“…We introduced the mutant plasmid DNA into R-1 with a Sigma-Aldrich yeast transformation kit. Genetic testing confirmed that the construct was correctly inserted (17).…”
Section: Methodsmentioning
confidence: 82%
“…Assay of ATPase Activity-We measured Pdr5-specific ATPase activity as described previously (12) for 8 min at 35°C with 12 g of purified PM vesicle protein derived from cells bearing two copies of either WT or mutant PDR5 genes (17). We verified all ATPase results by carrying out assays with at least two independent PM vesicle preparations/strain.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations